The westernmost records of extinct large European tortoises: the presence of Titanochelon (Testudinidae) in the Miocene of Portugal. (18th August 2017) - Pérez-García, A.; Vlachos, E.; Mocho, P.
Abstract: The information about the European giant fossil tortoises has been greatly increased in recent years, based on the description of new material and the revision of previously published specimens. A genus with a wide paleobiogeographic and stratigraphic distribution, Titanochelon, has recently been described, containing all large testudinids from the European Neogene record. Its type species, Titanochelon bolivari, was described in the Spanish record. The presence of this species outside this country had not been justified. In this paper we present and describe fossil material of large testudinids from several sites in the Lisbon District (Portugal), from lower (Quinta da Barbacena; MN4), middle (Charneca do Lumiar and Quinta da Farinheira; MN5) and upper (Aveiras de Baixo; MN9) Miocene levels. This study allows us to confirm the presence of Titanochelon in the Portuguese record and justify, for the first time, the presence of Titanochelon bolivari outside Spain. Furthermore we are able to discuss the geographical and temporal distribution of the large tortoises in the middle Miocene of Europe, a relevant period for the diversity and evolution of this clade.